2014
DOI: 10.1016/j.neo.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 Promotes Malignancy in Glioblastoma by Regulating Plasticity and Astrocytic Differentiation

Abstract: The high-mobility group-box transcription factor sex-determining region Y-box 2 (Sox2) is essential for the maintenance of stem cells from early development to adult tissues. Sox2 can reprogram differentiated cells into pluripotent cells in concert with other factors and is overexpressed in various cancers. In glioblastoma (GBM), Sox2 is a marker of cancer stemlike cells (CSCs) in neurosphere cultures and is associated with the proneural molecular subtype. Here, we report that Sox2 expression pattern in GBM tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 47 publications
15
111
0
Order By: Relevance
“…S6). These findings are consistent with our RNA-seq analysis and with previous published results showing that SOX2 is widely expressed in primary glioma, but is reduced in recurrent glioma (22).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…S6). These findings are consistent with our RNA-seq analysis and with previous published results showing that SOX2 is widely expressed in primary glioma, but is reduced in recurrent glioma (22).…”
Section: Discussionsupporting
confidence: 94%
“…These findings suggest that the NE regions of proneural gliomas predominantly contain OLIG2 + , OPC-like glioma cells, whereas NE regions of mesenchymal gliomas contain a larger proportion of CD44 + astrocyte-like tumor cells. Notably, Sox2, a proneural classifier gene and stem cell marker that has been implicated in glioma growth and progression (21,22) is expressed by both OLIG2 + cells and CD44 + cells. Immunohistochemical stains of NE glioma samples showed that SOX2 is expressed in a high percentage of infiltrating glioma cells in primary samples; however, recurrent gliomas showed a significantly lower SOX2 labeling index (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7 Translocations involving NCOA2 have been observed in mesenchymal chondrosarcoma, spindle cell rhabdomyosarcoma, prostate cancer, colon cancer, acute leukemia, and soft tissue angiofibroma, whereas ETV3 abnormalities have been For [6][7][8][9] Neoplastic associations of ICH are limited to case reports that include patients with mast cell leukemia, acute myeloid leukemia, and B-cell lymphoma.…”
mentioning
confidence: 99%
“…An embryonic stem cell gene signature is well known to correlate with a more undifferentiated phenotype in various cancers (28), and a large scale tissue microarray analysis including 80 low-grade and 98 high-grade gliomas showed an upregulated protein level of NANOG, KLF-4, OCT-4 and SOX-2 in highgrade gliomas (29). Several other studies also point to the relevance of neural and embryonic stem cell markers in GBM progression (30)(31)(32)(33)(34)(35)(36). In the present study we showed that both neural and embryonic stem cells markers are preferentially co-expressed with CXCR4 in matched samples of primary and recurrent GBM pairs, whereas CXCR7 was mostly found on stem cell marker negative cells.…”
Section: Discussionmentioning
confidence: 95%